Empirical Analysis of Homebuyers’ Real Estate Disputes: Insights from Coimbatore and Tiruppur Districts - Prabagar, M.; Sunanda Bhagavathy, P.G.; Anantharamakrishnan, S. (Journal of Neonatal Surgery, 2025)
This study examines the multifaceted real estate disputes faced by homebuyers in the Coimbatore and Tiruppur districts. Using data collected from 82 homebuyers through structured surveys and interviews, this paper analyzes disputes across categories such as project delays, non-compliance with agreements, discrepancies in promised amenities, possession and handover disputes, and more under the Real Estate (Regulation and Development) Act (RERA). Statistical tools, including reliability analysis, t-tests, and one-way ANOVA, were employed to understand how socio-demographic factors and property characteristics influence dispute perceptions. The findings reveal nuanced trends, providing actionable insights for policymakers, real estate developers, and regulatory authorities.